Spectral Studies on Metal Complexes of a Newly Synthesized Azetidinone - KUMAR, DINESH; SYAMAL, ARUN; KUMAR, AMIT; DASS, DURGA; GUPTA, ANJU (Asian Journal of Chemistry, 2010)
A dioxane solution of N-(4-amino-5-methyl-3-thiohydroxy-1,2,4- triazole)-3¢-carboxy-2¢-hydroxybenzalideneimine, LH3 (I) on reacting with chloroacetyl chloride, in the presence of triethylamine, undergoes cyclization to form N-(4-amino-5-methyl-3-thiohydroxy-1,2,4-triazole)- 4-(3'-carboxy-2'-hydroxyphenyl)azetidin-2-one, L'H3 (II). A methanolic solution of L'H3 reacts with Mn(II), Co(II), Ni(II), Cu(II), Zn(II), Cd(II), Fe(III), Zr(IV), MoO2(VI) and UO2(VI) ions to form the complexes, [M(L'H)·MeOH]2 [where M = Mn(II), Co(II) or Ni(II)]; [Cu(L'H)]2; [M(L'H)] [where M = Zn(II), Cd(II), MoO2(VI) or UO2(VI)]; [Fe(L'H)Cl]2 and [Zr(OH)2(L'H)]2. The compounds have been characterized on the basis of elemental analyses, molar conductance, molecular weight, spectral (IR, UV-visible) studies and magnetic susceptibility measurements. L'H3 behaves as a dibasic tridentate OON donor ligand in [Cu(L'H)]2, while it acts as a dibasic tetradentate OONS donor ligand in rest of the compounds. The complexes, [M(L'H)·MeOH]2 [M = Mn(II), Co(II) or Ni(II)]; [Cu(L'H)]2; [Fe(L'H)Cl]2 and [Zr(OH)2(L'H)]2 are dimers, while others are monomers. The dimeric complex, [Cu(L'H)]2 exhibits subnormal magnetic moment and is involved in antiferromagnetic exchange, while all other complexes are magnetically dilute. The octahedral structure for Mn(II), Co(II), Ni(II), Fe(III), MoO2(VI) and UO2(VI) complexes, square planar structure for Cu(II) complex, tetrahedral structure for Zn(II) and Cd(II) complexes and pentagonal bipyramidal structure for Zr(IV) complex have been suggested.